Myocardial work in electrical dyssynchrony due to left bundle branch block - E. M. Rimskaya; S. V. Dobrovolskaya; E. V. Kukharchuk; S. Yu. Kashtanova; N. A. Mironova; G. S. Tarasovsky; A. E. Komlev; T. E. Imaev; M. A. Saidova; S. P. Golitsyn (Российский кардиологический журнал)
Aim. To evaluate myocardial function in different groups of patients with left bundle branch block (LBBB) and the LBBB "model" — right ventricular pacing (RVP).Material and methods. Global longitudinal strain (GLS) and myocardial function parameters, such as global constructive work (GCW), global wasted work (GWW), global work index (GWI), and global work efficiency (GWE), were measured in 25 patients with dilated cardiomyopathy (DCM) and LBBB (DCM-LBBB group), 20 patients with DCM and a narrow QRS complex (DCM-nonLBBB group), 15 patients with LBBB developed after transcatheter aortic valve implantation (TAVI LBBB group), 12 patients with idiopathic LBBB (I-LBBB group), 27 patients with permanent RVP, and 10 healthy volunteers (HVs). The segments with maximum and minimum GWI were determined in all patients.Results. The GLS, GWI and GCW values were comparable in the I-LBBB and RVP groups, and were significantly lower in the TAVI-LBBB and both DCM groups than in HVs (p=0,049, 0,006, 0,025; p<0,001, respectively). Patients in the I-LBBB, TAVI-LBBB, RVP and DCM-LBBB groups were characterized by an increased GWW value (261 [203,5; 291,5], 273 [184,8; 385,3] and 237 [149,5; 445,3] versus 108 [74,3; 137,3] mm Hg%, p=0,033, 0,006, <0,001, <0,001, respectively), while the GWW value in the DCM-LBBB group was the highest (346,5 [255,5; 437,8] mm Hg%). The GWW value was associated with the QRS width (r=0,456, p<0,001). The GWE value was reduced in the I-LBBB, TAVI-LBBB, RVP and DCM-LBBB groups compared to HVs (p=0,033, 0,007, 0,023, <0,001, respectively). The area of maximum GWI was located in the posterolateral wall, and the minimum GWI in the interventricular septum in most patients with LBBB, while in the RVP group it was very diverse.Conclusion. Despite the fact that all patients with an electrical activation pattern corresponding to LBBB are characterized by significant wasted work, its contribution to the global myocardial work is significant only in patients with DCM. Lost work does not lead to a decrease in constructive work in patients with I-LBBB and RVP and normal left ventricular systolic function.